Measurement of the ratio of branching fractions B(B[bar]0→D*+τ-ν[bar]τ)/B(B[bar]0→D*+μ-ν[bar]μ) - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Physical review letters, 2015)
The branching fraction ratio R(D∗)≡B(¯B0→D*+τ−¯ντ)/B(¯B0→D*+μ−¯νμ) is measured using a sample of proton-proton collision data corresponding to 3.0 fb−1 of integrated luminosity recorded by the LHCb experiment during 2011 and 2012. The tau lepton is identified in the decay mode τ−→μ−¯νμντ. The semitauonic decay is sensitive to contributions from non-standard-model particles that preferentially couple to the third generation of fermions, in particular, Higgs-like charged scalars. A multidimensional fit to kinematic distributions of the candidate ¯B0 decays gives R(D∗)=0.336±0.027(stat)±0.030(syst). This result, which is the first measurement of this quantity at a hadron collider, is 2.1 standard deviations larger than the value expected from lepton universality in the standard model.